Impact of Multivessel Revascularization on Health Status Outcomes in Patients with ST-Elevation Myocardial Infarction and Multivessel Coronary Disease - Jang, Jae-Sik (J Am Coll Cardiol, 2015)
BACKGROUND: Up to 65% of patients with ST-elevation myocardial infarction (STEMI) have multivessel coronary disease (MVCAD). TLong-term health status of STEMI patients following multivessel revascularization is unknown. OBJECTIVE: We investigated the relationship between multivessel revascularization and health status outcomes (symptoms and quality of life [QoL]) in STEMI patients with MVCAD. METHODS: Using a U.S. myocardial infarction registry and the Seattle Angina Questionnaire (SAQ), we determined the health status of patients with STEMI and MVCAD at the time of STEMI and 1 year later. We assessed the association of multivessel revascularization during index hospitalization with 1-year health status using multivariable linear regression analysis, and also examined demographic, clinical, and angiographic factors associated with multivessel revascularization. RESULTS: Among 664 STEMI patients with MVCAD, 251 (38%) underwent multivessel revascularization. Most revascularizations were staged during the index hospitalization (64.1%), and 8.0% were staged after discharge, with 27.9% performed during primary PCI. Multivessel revascularization was associated with age and more diseased vessels. At 1 year, multivessel revascularization was independently associated with improved symptoms (4.5 points higher SAQ angina frequency score; 95% CI: 1.0 to 7.9) and QoL (6.6 points higher SAQ QoL score; 95% CI: 2.7 to 10.6). One year mortality was not different between those who did and did not undergo multivessel revascularization (3.6% vs. 3.4%; log-rank test p = 0.88). CONCLUSIONS: Multivessel revascularization improved angina and QoL in STEMI patients with MVCAD. Patient-centered outcomes should be considered in future trials of multivessel revascularization.